1977
DOI: 10.1242/jcs.26.1.359
|View full text |Cite
|
Sign up to set email alerts
|

5-bromodeoxyuridine-induced formation of virus-like particles in Naegleria Gruberi EGS

Abstract: Exposure of axenic cultures of the amoeboflagellate Naegleria gruberi EGs to the thymidine analogue 5-bromo-2′-deoxyuridine (BrdU) resulted in the induction of virus-like particles (VLP) and various structures associated with their development and presumed transmission. Previously, VLP induction could be accomplished only by growing amoebae in the presence of living bacteria as a food source. Addition of excess thymidine along with BrdU did not block induction of particles. This account demonstrates that the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…By scrupulous electron-microscopy studies the authors established that VLPs can, first of all, be found in the nucleus of this protozoon. From there they move to the cytoplasm most probably through channels of nucleic membrane (Schuster, Dunnebacke, 1976). F. L. Schuster and T. H, Dunnebacke in their experiments with N. gruberi observed rupture of the nucleic membrane as it had been described by L. S. Diamond et al (1972) in E. histolytica when the filamentous virus was released from the nucleus.…”
mentioning
confidence: 69%
See 4 more Smart Citations
“…By scrupulous electron-microscopy studies the authors established that VLPs can, first of all, be found in the nucleus of this protozoon. From there they move to the cytoplasm most probably through channels of nucleic membrane (Schuster, Dunnebacke, 1976). F. L. Schuster and T. H, Dunnebacke in their experiments with N. gruberi observed rupture of the nucleic membrane as it had been described by L. S. Diamond et al (1972) in E. histolytica when the filamentous virus was released from the nucleus.…”
mentioning
confidence: 69%
“…The fact that VLPs in the axenic cultures of N. gruberi were observed neither in the nucleus nor in associating bodies in the cytoplasm brought F. L. Schuster (1969) to the thought that the formation of these particles might be induced with bacteria. Grounding on the results of further investigations F. L. Schuster and T. H. Dunnebacke (1976), how-ever, expressed an opinion that VLPs exist in the nucleus latently and become manifest simultaneously with associating bodies in the cytoplasm only after certain metabolic changes. It was established that the number of amoebae with VLPs depends upon the ratio of amoebae to bacteria, since after the decrease of the bacterial admixture in the medium the VLPs appeared at first in the nucleus of some amoebae only (ca in 5 per cent), but at the further decrease of the amount of bacteria the number of amoebae with VLPs began constantly growing, reaching even as much as 50 per cent in the culture.…”
mentioning
confidence: 98%
See 3 more Smart Citations